Low temperature upregulates cwp expression and modifies alternative splicing patterns, increasing the severity of cwp-induced tomato fruit cuticular microfissures. Issue 1 (8th November 2019) - Chechanovsky, Noam; Hovav, Ran; Frenkel, Rina; Faigenboim, Adi; Eselson, Yelena; Petreikov, Marina; Moy, Michal; Shen, Shmuel; Schaffer, Arthur A
Abstract: The cwp (cuticular water permeability) gene controls the development of cuticular microfissuring and subsequent fruit dehydration in tomato. The gene underwent silencing in the evolution of the fleshy cultivated tomato but is expressed in the primitive wild tomato relatives. The introgression of the expressed allele from the wild S. habrochaites ( cwp h ) into the cultivated tomato ( Solanum lycopersicum ) leads to the phenotype of fruit water loss during and following ripening. In this report, we show that low temperature impacts on the severity of the cuticular microfissure phenotype via a combination of effects on both expression and alternative splicing of cwp h . The cwp gene, comprising four exons and three introns, undergoes post-transcriptional alternative splicing processes, leading to seven alternative transcripts that differ in reading-frame lengths. Transgenic plants expressing each of the alternative transcripts identified the longest reading frame (VAR1) as the functional splice variant. Low temperature led to a strong upregulation of cwp h expression, compounded by an increase in the relative proportion of the functional VAR1 transcript, leading to increased severity of microfissuring of the cuticle. In summary, we demonstrate the molecular mechanism behind the horticultural phenomenon of the low-temperature effect on cuticular microfissures in the dehydrating tomato.